A heavy metal-free CuInS2 quantum dot sensitized NiO photocathode with a Re molecular catalyst for photoelectrochemical CO2 reduction. Issue 55 (19th June 2019) - Huang, Jing; Xu, Bo; Tian, Lei; Pati, Palas Baran; Etman, Ahmed S.; Sun, Junliang; Hammarström, Leif; Tian, Haining
Abstract : Heavy metal-free CuInS2 QDs as a photosensitizer and a Re molecular catalyst have been successfully employed to co-sensitize a NiO photocathode for CO2 reduction into CO. Abstract : Heavy metal-free CuInS2 quantum dots (QDs) were employed as a photosensitizer on a NiO photocathode to drive an immobilized molecular Re catalyst for photoelectrochemical CO2 reduction for the first time. A photocurrent of 25 μA cm −2 at −0.87 V vs. NHE was obtained, providing a faradaic efficiency of 32% for CO production.